2013
DOI: 10.1186/1687-9856-2013-19
|View full text |Cite
|
Sign up to set email alerts
|

Towards identification of molecular mechanisms of short stature

Abstract: Growth evaluations are among the most common referrals to pediatric endocrinologists. Although a number of pathologies, both primary endocrine and non-endocrine, can present with short stature, an estimated 80% of evaluations fail to identify a clear etiology, leaving a default designation of idiopathic short stature (ISS). As a group, several features among children with ISS are suggestive of pathophysiology of the GH–IGF-1 axis, including low serum levels of IGF-1 despite normal GH secretion. Candidate gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…ISS is thought to be a polygenic disease, both genetic and environmental factors contribute to its pathogenesis, but genetic factors play a more significant part in the development of ISS [22]. Previous reports have shown that mutations in the genes along the GH-IGF axis and genes that regulate the development of the cartilage growth plate are involved in the development of ISS [4,23,24]. At present, studies are focused on the GH-IGF-1 axis genes, but from GWAS results, most genes and biological pathways associated with height were located in growth plate [21], such as BMP2, SOX8, WNT4, et al To reduce the expensive burden of growth hormone therapy,it's profitable to reveal the etiology of ISS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ISS is thought to be a polygenic disease, both genetic and environmental factors contribute to its pathogenesis, but genetic factors play a more significant part in the development of ISS [22]. Previous reports have shown that mutations in the genes along the GH-IGF axis and genes that regulate the development of the cartilage growth plate are involved in the development of ISS [4,23,24]. At present, studies are focused on the GH-IGF-1 axis genes, but from GWAS results, most genes and biological pathways associated with height were located in growth plate [21], such as BMP2, SOX8, WNT4, et al To reduce the expensive burden of growth hormone therapy,it's profitable to reveal the etiology of ISS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that hypothalamic-pituitary-gonadal (HPG) axis and growth hormone-Insulin-like growth factor (IGF) axis is the most vital hormonal axis governing growth [3]. Any level of abnormality of GH-IGF axis may cause short stature [4], such as GHR [5], IGF-1R [6,7], IGFALS [8] were associated with ISS, but fewer studies have investigated the association of HPG axis with the risk of ISS.…”
Section: Introductionmentioning
confidence: 99%
“…Following ligation, activation of Janus kinase 1 (JAK1) and 2 (JAK2) leads to subsequent activation of the Signal transducer and activator of transcription 1 (STAT1), 3 (STAT3), and 5 (STAT5). JAK2 and STAT5B have been shown to be indispensable for growth hormone‐mediated induction of IGF‐1, the principle transcriptional target required for growth, and lesions in this axis are associated with short stature . Given the known importance of JAK/STAT signaling in the human immune system and the role of STAT5 in lymphocyte proliferation and regulatory T cell development, one might have anticipated that a number of single gene disorders would be identified in which atopic and growth phenotypes coexist (Figure ).…”
Section: Allergic Disease a Growing Problemmentioning
confidence: 99%
“…Beyond these research-project-focused communities, other common bioinformatics-related activities are carried out in communities including professional/career development (especially training and education) or tool and resource development. Examples of such development-focused communities include interactions between groups of fellows and students (e.g., ISCB Student Council and Regional Student Groups [RSGs] [ 22 ] or the Software Sustainability Institute's [SSI] [ 23 ] Fellowship Program http://www.software.ac.uk/fellowship-programme ), local geographically-focused groups of bioinformaticians (e.g., TorBUG http://www.torbug.org or Heidelberg Unseminars in Bioinformatics [HUB] [ 24 ] http://www.hub-hub.de ), bioinformatics trainers and educators (e.g., GOBLET [ 25 ]), heads of nodes and technical coordinators involved in bioinformatics infrastructure development and capacity building (e.g., ELIXIR http://www.elixir-europe.org or H3ABioNet http://www.h3abionet.org ), and cooperations between software/tool developers and their larger user communities (e.g., Bioconductor [ 9 ] or Galaxy [ 7 , 8 , 26 ]).…”
Section: Benefits Of Participating In Bioinformatics Communities: Oppmentioning
confidence: 99%